Chronic osteomyelitis in systemic lupus erythematosus: Diagnostic and therapeutic pitfalls - Insanfadhil, Muhammad; Rahman, Perdana (Deka in Medicine, 2025)
BACKGROUND: Chronic osteomyelitis is a recalcitrant and difficult-to-treat bone infection, particularly in immunocompromised individuals such as patients with Systemic Lupus Erythematosus (SLE). The coexistence of chronic osteomyelitis with SLE and malnutrition is clinically rare. This article aims to describe the diagnostic approach and conservative management of chronic osteomyelitis in a patient with SLE. CASE: A 19-year-old female presented with a two-week history of medial left knee pain, progressive swelling, and difficulty walking. The symptoms had recurred intermittently since November 2020, initially beginning with swelling and ulceration, and later developing into purulent discharge. Physical examination revealed swelling from the medial to posterior aspect of the left knee, tenderness, and reduced range of motion. Radiographic imaging demonstrated bone destruction in the proximal third of the left tibia, consistent with chronic osteomyelitis. A previous wound culture showed growth of antibiotic-sensitive bacteria. The patient was also diagnosed with SLE in remission, malnutrition (BMI <18), and an asymptomatic urinary tract infection. She was treated conservatively with oral antibiotics based on culture results, nutritional supplementation, and continued immunosuppressive therapy. Follow-up demonstrated clinical improvement without systemic infection or new local complications. CONCLUSION: Chronic osteomyelitis in malnourished patients with SLE can be successfully managed with a conservative treatment approach. Comprehensive evaluation and long-term follow-up are essential to minimize the risk of recurrence and complications.